APPLICATION OF LINGUISTOCRIBAL CAPABILITIES OF DIGITAL TECHNOLOGIES AND PEDAGOGICAL METHODS IN THE PROCESS OF TRAINING FUTURE LEADERS (Educator Insights: Journal of Teaching Theory and Practice, 2025)
This article explores the theoretical and practical aspects of applying digital technologies and modern pedagogical methods in the linguodidactic training of future leaders. In today's era of globalization, leaders’ language proficiency, digital literacy, and communication skills are crucial for interorganizational cooperation and management efficiency. Therefore, digital platforms, interactive resources, AI-based systems, mobile applications, and multimedia tools are widely used to enhance the linguistic preparedness of future leaders. The article scientifically analyzes the integration of these technologies into the educational process, their alignment with pedagogical approaches, and their impact on learners’ motivation, language competence, and managerial potential.